SIMPLE BIOANALYTICAL QUANTIFICATION METHOD FOR SIMULTANEOUS ESTIMATION OF SIMVASTATIN AND EZETIMIBE IN HUMAN PLASMA BY REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY TECHNIQUE - DYADE GK; SAWANT RL (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: A bioanalytical quantification method was developed for the simultaneous estimation of simvastatin (SIM) and ezetimibe (EZE) from the human plasma. Methods: The technique was developed and equipped with reverse-phase (RP) high-performance liquid chromatography, using RP-C18 column with an ultraviolet detector. For the estimation of SIM and EZE, the mobile phase (acetonitrile:acetate buffer pH 4.0, pH adjusted with acetic acid) was pumped at a flow rate of 0.8 ml/min in the ratio of 85:15% v/v and the eluents were monitored at 234 nm. A calibration graph to study linearity of the SIM and EZE in biological matrix was carried out in the concentration range of 400–4000 ng/ml for both these drugs SIM and EZE. Results: The developed method was validated according to the US FDA and European Medicines Agency guidelines for sensitivity, accuracy, precision, and stability. The obtained statistical data of validation were found to be within prescribed limit assures rigidity of the method. Both the drugs in combined form were estimated in human plasma by the proposed method. Conclusions: The developed method is free from solid-phase extraction so it becomes simple and economical. The method is efficient for precise and accurate quantification of SIM and EZE in plasma and hence applied for bioequivalence, bioavailability study in real clinical samples.